Analisis Karakteristik Perekonomian Berbasis Kearifan Lokal pada Masyarakat Kampung Naga Desa Neglasari Kecamatan Salawu - Elan Artono Nurdin; Era Iswara Pangastuti; Saffina Eka Rahma Wati; Mohammad Iqbal Dhayfullah; Anis Watin Faizah (Geography Education Study Program, Universitas Kanjuruhan Malang, 2023)
Kampung Naga is a traditional village that is quite unique in that it still maintains its local wisdom and culture to this day. The local wisdom that exists in Kampung Naga regulates all activities of the community itself and is comprehensive from various aspects, including the economic conditions of the community. The purpose of this study was to determine the economic characteristics of the Kampung Naga community. To find out these characteristics the research method used is a qualitative description method. From the results of the study it was found that the economic characteristics of the Kampung Naga community were still very traditional and simple and put forward the concept of kinship and mutual cooperation.